Apakah Ukuran Perusahaan dan Kinerja Keuangan Mempengaruhi Perusahaan dalam Mengungkapkan Sustainability Report ? - Dwi Indah Lestari; Merta Noer Vadila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
One way to increase corporate awareness and responsibility for the environment can be done through Sustainability reports. The purpose of this study is to analyze the effect of company size and financial performance on the disclosure of Sustainability Reports on non-financial sector companies listed on the Stock Exchange in 2017-2018 both partially and simultaneously. Company size is measured using total assets while financial performance is measured using the ratio of Return on Assets. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX) and uses an associative descriptive method with a quantitative approach. This research uses purposive sampling method. The results of this study indicate that both partially and simultaneously, company size and financial performance do not significantly influence the disclosure of Sustainability Report elements. Keywords : Sustainability Report, Companies’ size, Financial Performance